Functional and transcriptional differences in monocytes from children with obesity compared to children of healthy weight. (14th October 2021) - Bekkering, S; Saner, C; Novakovic, B; McCallum, Z; Netea, M G; Riksen, N P; Sabin, M A; Saffery, R; Burgner, D P
Abstract: Background and aim: Cardiometabolic risk accrues across the entire life course and childhood is a key epoch for effective prevention. Obesity in childhood is the most prevalent modifiable risk factor for later cardiovascular disease (CVD). Inflammatory biomarkers and innate immune capacity are increased in adults with obesity, but childhood data are scarce. We aimed to investigate (i) innate immune cell activation in children with and without obesity; and (ii) whether weight loss impacts the innate immune inflammatory phenotype. Methods: The innate immune phenotype of Peripheral Blood Mononuclear Cells (PBMCs) from 31 children with obesity (BMI z-score>2.5) and 22 children of healthy weight (−1.5≤BMIz≤1.5, sex, age and pubertal stage matched) was characterized by high dimensional flow cytometry, ex vivo stimulation assays with subsequent 27-plex cytokine measurements, and transcriptome analysis using RNA sequencing (Figure 1). Children with obesity participated to the Royal Children's Hospital Weight Management Service (median 5 years) and at follow-up, PBMCs were obtained again as well as anthropometric data and subclinical cardiovascular phenotypes. Results: Flow cytometric analysis showed marked differences in cell composition between children with obesity and children of healthy weight. Specifically, children with obesity have significant changes in monocyte subsets and an increased expression of monocyte activation markers. Upon stimulation, monocytes of children with obesity show an increased cytokine production capacity. Finally, transcriptomic analysis shows significant differences between monocytes from obese children and healthy controls. Effects of weight loss on these immune parameters and correlations with preclinical CVD phenotypes are currently being analysed. Conclusions: Monocytes from children with obesity have a pro-inflammatory phenotype compared to children of normal weight. Heightened inflammation may contribute to increased CVD risk later in life and may offer opportunities for early intervention. FUNDunding Acknowledgement: Type of funding sources: Other. Main funding source(s): Dutch Scientific Organisation (NWO) - Rubicon grant to S.B. Dutch Heart Foundation - CVON IN CONTROL II to N.P.R. and D.B.